Improving the uptake of predictive testing and colorectal screening in Lynch syndrome: a regional primary care survey. (4th February 2015) - Barrow, P.; Green, K.; Clancy, T.; Lalloo, F.; Hill, J.; Evans, D.G.
<x xml:space="preserve">Abstract</x> Lynch syndrome (LS) is an autosomal dominant cancer predisposition syndrome with a 60–80% lifetime risk of colorectal cancer. We assessed the uptake of predictive testing and colorectal screening among first‐degree relatives (FDRs) in LS families and explored novel methods for informing and engaging at‐risk relatives. Uptake of predictive testing was explored using Kaplan–Meier analysis and engagement with colorectal screening was ascertained. A questionnaire was distributed to 216 general practitioners (GPs) of registered LS family members to determine their prior experience and opinion of an enhanced role. Of 591, 329 (55.7%) FDRs had undergone predictive testing. Uptake was significantly lower in males (p = 0.012) and individuals <25 years (p < 0.001). Mutation carriers were more likely to undergo colorectal screening than untested FDRs (97.2% vs 34.9%; P ≤ 0.0001). Of 216, 63 (29.2%) questionnaires were returned. Most GPs (55/63; 87.3%) were not confident to discuss the details of LS with patients and relatives. The main barriers were lack of knowledge and concerns about confidentiality. Compliance with colorectal screening is excellent following a mutation positive predictive test. Uptake of predictive testing could be substantially improved, particularly among males and younger age groups. GPs are unlikely to actively participate in communication with at‐risk relatives without considerable support.